2014
DOI: 10.4238/2014.march.12.9
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and apoptosis in the fetal and neonatal ovary of guinea pigs

Abstract: ABSTRACT. The guinea pig is an excellent animal model for studying reproductive biology of adult humans and most domestic animals. Yet, whether this animal might serve as a good model for embryonic stage investigations and determinations of signals affecting or directing ovary development remains unknown. These questions were addressed by examining morphological evolution and the expression of biomarkers of cell proliferation and apoptosis in the ovaries of fetal and neonatal guinea pigs in the present study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The ovary follicular period of guinea pigs is very similar to that of humans (van Kan et al, 2009), and they are therefore very good animal models for research on human propagation (Kulduk et al, 2014;Sun et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…The ovary follicular period of guinea pigs is very similar to that of humans (van Kan et al, 2009), and they are therefore very good animal models for research on human propagation (Kulduk et al, 2014;Sun et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…It was confirmed that a CL-like structure has a significantly lower number of luteinized cells and higher proportion of apoptotic luteinized cells. Cell differentiation and proliferation contribute to follicular formation (Sun et al, 2014). However, the source of differentiated cells is unclear: they may rapidly differentiate from basal membrane cells after apoptosis of granulosa cells, or they may differentiate and proliferate from theca and granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Guinea pigs are a more reliable reproductive model as compared with mice or rats (Silva et al, 1998;Shi et al, 1999;Kulduk et al, 2014;Sun et al, 2014), because they share similarities with humans and large domestic animals in estrous cycles and prolonged pregnancy (van Kan et al, 2009). Guinea pigs, only ovulate a few oocytes (3.6±0.1) in one typical estrous cycle (Suzuki et al, 1993), and the majority of follicles are lost by atresia (Hermreck and Greenwald, 1964) in the four continuous stages (Wang et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the proliferation of granulosa cells has been believed as a vital regulatory factor during the development of ovarian follicles and proliferation cell nuclear antigen (PCNA) was widely used as cell proliferation marker in many lectures [5]. Therefore, the present study used a HIF1alpha small-molecule inhibitor echinomycin (Ech) and a follicular development model of postnatal rats to investigate the contribution of HIF-1alpha to ovarian follicular development through examining the changes of HIF-1alpha and PCNA during the follicular development based on the follicular development characteristics of the model animals in order to further understanding the regulatory mechanism of the follicular development in mammalian ovary.…”
Section: Introductionmentioning
confidence: 99%